Randomized clinical trial comparing self‐gripping mesh with suture fixation of lightweight polypropylene mesh in open inguinal hernia repair. Issue 11 (21st August 2014) - Sanders, D. L.; Nienhuijs, S.; Ziprin, P.; Miserez, M.; Gingell‐Littlejohn, M.; Smeds, S.
<x xml:space="preserve">Abstract</x> Background Postoperative pain is an important adverse event following inguinal hernia repair. The aim of this trial was to compare postoperative pain within the first 3 months and 1 year after surgery in patients undergoing open mesh inguinal hernia repair using either a self‐gripping lightweight polyester mesh or a polypropylene lightweight mesh fixed with sutures. Methods Adult men undergoing Lichtenstein repair for primary inguinal hernia were randomized to ProGrip™ self‐gripping mesh or standard sutured lightweight polypropylene mesh. Results In total 557 men were included in the final analysis (self‐gripping mesh 270, sutured mesh 287). Early postoperative pain scores were lower with self‐gripping mesh than with sutured lightweight mesh: mean visual analogue pain score relative to baseline +1·3 and +8·6 respectively at discharge (P = 0·033), and mean surgical pain scale score relative to baseline +4·2 and +9·7 respectively on day 7 (P = 0·027). There was no significant difference in mid‐term (1 month) and long‐term (3 months and 1 year) pain scores between the groups. Surgery was significantly quicker with self‐gripping mesh (mean difference 7·6 min; P < 0·001). There were no significant differences in reported mesh handling, analgesic consumption, other wound complications, patient satisfaction or hernia recurrence between the groups. Conclusion Self‐gripping mesh for open inguinal hernia repair was well tolerated and reduced early postoperative pain (within the first week), without increasing the risk of early recurrence. It did not reduce chronic pain. Registration number: NCT00827944 (http://www.clinicaltrials.gov).